Perbedaan Pendapatan dan Kelayakan Usaha Penangkapan Rajungan dengan Alat Tangkap Bubu dan Jaring Insang - Waode Nurmalisa; Budiyanto Budiyanto; Samsul Kamri (Jurnal Sosio Agribisnis, 2021)
This study aims to determine the differences in the income of small crabs fishing between those using traps and gill nets, and to determine the feasibility of catching small crabs. The study was conducted in March 2020 in Bajo Indah Village, Soropia Subdistrict, Konawe Regency. The population in this study, for trap fishermen as many as 25 people and gill net fishermen as many as 25 people. The sampling method was cluster random sampling. The number of samples for trap fishermen is 10 people and gill nets are 10 people. The data collected is the number of inputs, outputs, costs, revenues, and incomes. Data collection was carried out by means of interviews and documentation. Data analysis used the t-test with a confidence level of 95 percent or α = 0.05. The results of the study show that the income of small crab fishing between those using traps and gill nets is significantly different. The business of catching small crabs using gill net fishing gear is more feasible to operate than traps.Keywords: crab; traps and gill nets; income; different tests; feasibility